Longevity, fertility and economic growth: Do environmental factors matter? - Varvarigos, Dimitrios; Zakaria, Intan Zanariah (Wiley, 2017)
Our study examines the effect of environmental factors on the economic decisions regarding fertility. We incorporate health-damaging pollution into a three period overlapping generations model in which life expectancy, fertility and economic growth are all endogenous. We show that environmental factors can cause significant changes to the economy’s demographics. In particular, the entrepreneurial choice of less polluting production processes, induced by a tax on emissions, can at some point in time lead to such changes as higher longevity and lower fertility rates. Thus, we provide a novel explanation on the positive relation between fertility rates and pollution. According to this, the causality on this relation may also work from the latter to the former. Furthermore, our model can account for the empirically observed N-shaped correlation between pollution and income per capita.